Quality control in bioassays used in screening for plant viruses1. (16th July 2013) - Roenhorst, J. W.; Botermans, M.; Verhoeven, J. T. J.
Abstract : Test plants are often used for broad screening for plant viruses. Mechanical inoculation of a series of test plants enables generic detection of mechanically transmitted viruses in only 1 assay. Moreover, such an assay is suitable for known as well as unknown viruses and their variants. However, in comparison to serological and molecular methods, quality control in bioassays is almost never addressed. The system of positive and negative controls, blind samples and proficiency tests is applicable, provided that a broader interpretation of positive and negative controls is used. For validation, performance criteria can only be determined for individual viruses. However, results can often be extrapolated. Sensitivity is addressed by dilution and expressed as a relative value. Specificity has to consider the virus species and the plant species to be tested. Selectivity mostly depends on the plant species tested, because some hosts contain components that inhibit transmission. Repeatability and reproducibility, determined for a limited number of samples, appears high, as also substantiated by the authors' experience. This paper details how EPPO Standards on quality control were implemented by the National Plant Protection Organization of the Netherlands (NPPO‐NL). This information will be of use for other laboratories that wish to introduce quality control in bioassays for virus testing.